Effects of hyperbaric oxygen therapy on recovery after a football match in young players: a double-blind randomized controlled trial - Gušić, Marko; Stantić, Tomislav; Lazić, Anja; Andrašić, Slobodan; Roelands, Bart; Bogataj, Špela (Frontiers in Physiology, 2024)
Football is a physically demanding sport that requires effective recovery strategies to maintain performance level and prevent injuries. This study investigated if of a single one-hour hyperbaric oxygen therapy (HBOT) session affects recovery and performance after a football match in elite youth players. Twenty elite youth football players (age 17.3 ± 0.5 years) were randomly assigned to a HBOT group or a control group (CON). They played a 90-min football game and underwent either a 60-min HBOT or placebo intervention. Before (T1), at the end of the match (T2), one hour after HBOT or CON session (T3), and 12 hours after HBOT session (T4), subjects underwent biochemical (serum samples (myoglobin (MB), creatine kinase (CK), lactate dehydrogenase (LDH), alanine aminotransferase (ALT), and aspartate aminotransferase (AST)) and performance measurements (linear speed at 5m, 10m and 20m, squat jump (SJ), countermovement jump (CMJ) and countermovement jump with arm swing (CMJa)). The Hooper Index (HI) was collected and heart rate was measured during the game. The football match induced significant increases in all biochemical markers, but no significant differences were found between the HBOT and control group in biochemical or performance parameters at any time point. However, there was a significant interaction effect between time and group for HI (p = 0.012, η2 = 0.124), with the HBOT group showing significantly lower HI values (8.6 ± 2.41) than the control group (11.0 ± 3.23) at one hour post-HBOT.A single one-hour session of HBOT did not significantly affect recovery or performance parameters in elite youth football players, though it did show a moderate positive effect affect on the Hooper IndexHI at one hour post-HBOT. Further studies should explore the impact of either longer or sequential HBOT sessions on recovery.